Please explain this one?

Attachment image

2 Answers

Relevance
  • Jim
    Lv 7
    1 month ago

    For  h(7n-5), sub that into the function for x

    h(x) = √(x+5)

    h(7n-5) = √((7n-5) -5)

    = √7n, n>0 ((for Real answers))

  • 1 month ago

    Again, exactly like your other questions:  substitute an expression in for the variable:

    h(x) = √(x + 5)

    Substitute (7n - 5) in for x and simplify:

    h(7n - 5) = √(7n - 5 + 5)

    h(7n - 5) = √(7n)

Still have questions? Get answers by asking now.